Development and Implementation of a Four-Tier Close-Ended Test to Analyze Students' Misconceptions of Optical Instruments - Astuti, Itsna Rona Wahyu; Samsudin, Achmad; Kaniawati, Ida; Suhendi, Endi; Çoştu, Bayram (Universitas Islam Negeri Raden Intan Lampung, 2023)
The research aims to develop a four-tier test for optical instrument materials. The method used in this study is a 4D design that includes defining, designing, developing, and disseminating. The instrument used consisted of fifteen items in the form of a four-tier closed-ended test. The research participants were 60 female and 15 male students from West Java in grade 11 high school who were randomly selected. The analysis is divided into four parts. The first analysis is a CVR and multi-rater Rasch measurement of the original validation results. The second analysis involves calculating the percentage of students' scores based on their conception scores. The third is a Rasch Model analysis of the instrument's validity and reliability. The Rasch Model is used in the fourth analysis to examine conceptions and misconceptions. Following the analysis, all items met the CVR value criteria. I2, I7, I9, I10, I12, I15, and I3 have logit values less than zero and are corrected based on expert feedback. The second analysis reveals that students continue to have misconceptions about each item. According to the third analysis, all items were valid and reliable, with a Cronbach Alpha value 0.78 in either category. According to the fourth analysis, conception is inversely related to misconception. The fewer misconceptions, the better the students' conceptions, and vice versa. However, confidence can also be a dissonant influence. Students who experience misconceptions need to be given appropriate treatment to reduce misconceptions about optical instrument materials. Hopefully, the four-tier closed-ended test that has been developed can be used and developed into a better five-level test to investigate the causes of each student's misconceptions.